Immune microenvironment in patients with mismatch‐repair‐proficient oligometastatic colorectal cancer exposed to chemotherapy: the randomized MIROX GERCOR cohort study. Issue 11 (9th February 2022) - Jary, Marine; Liu, Wen‐Wei; Yan, Dongyao; Bai, Isaac; Muranyi, Andrea; Colle, Elise; Brocheriou, Isabelle; Turpin, Anthony; Radosevic‐Robin, Nina; Bourgoin, Pierre; Penault‐Llorca, Frédérique; Cohen, Romain; et al.
Abstract : In the era of immune checkpoint inhibitors, understanding the metastatic microenvironment of proficient mismatch repair/microsatellite stable (pMMR/MSS) colorectal cancer (CRC) is of paramount importance to both prognostication and the development of more effective novel therapies. In this study, primary and paired metastasis tissue samples were collected from patients with resectable metastatic CRC treated with adjuvant FOLFOX or peri‐operative chemotherapy in the MIROX phase III prospective study. In total, 74 cancer tissues were stained for CD3, CD8, Forkhead box protein 3 (FOXP3), programmed cell death protein‐1 (PD‐1, invasive front, stromal, intra‐epithelial compartments), and programmed death‐ligand 1 (PD‐L1, tumor, immune cells). The immune profiling of primary CRC had a limited value to predict the immune context of paired metastases for all markers but CD3+. The expression of CD8 and PD‐L1 was higher in metastases after neoadjuvant FOLFOX. In metastases, both CD3 T cells at the invasive front and PD‐L1 expressions on immune cells were predictive of better disease‐free survival. These results show that the effect of FOLFOX on modifying the immune microenvironment in resected CRC metastases and measurement of PD‐L1 expression and tumor‐infiltrating CD8 T cells in pMMR/MSS metastatic tissue samples could improve treatment strategies of metastatic CRC patients. Abstract : Here, we characterized the immune microenvironment of proficient mismatch repair/microsatellite stable oligometastatic patients with colorectal cancer (CRC) treated with the neoadjuvant FOLFOX. Primary tumor immune profiling had limited predictive value in estimating the metastatic immune context. CD3 T cells and PD‐L1 immune cells at the invasive front were predictive of disease‐free survival. In addition, the expression of CD8 and PD‐L1 was higher after FOLFOX treatment. Thus, CD8 high /PD‐L1 high signature could be related to chemotherapy response and could improve treatment strategies of metastatic patients with CRC.